New sensible method to quantize the intestinal absorption of receptor ligands. Issue 15 (1st August 2019) - Buccioni, Michela; Dal Ben, Diego; Lambertucci, Catia; Martí Navia, Aleix; Ricciutelli, Massimo; Spinaci, Andrea; Volpini, Rosaria; Marucci, Gabriella
Graphical abstract: Abstract: In recent years, special attention has been paid to the A3 adenosine receptor (A3 AR) as a possible pharmacological target to treat intestinal inflammation. In this work, it was set up a novel method to quantify the concentration of a promising anti-inflammatory agent inside and outside of intestinal barrier using the everted gut sac technique. The compound chosen for the present study is one of the most potent and selective A3 AR agonist reported so far, named AR 170 (N 6 -methyl-2-phenylethynyl-5′- N -methylcarboxamidoadenosine). In order to evaluate the intestinal absorption of AR 170 the radioligand binding assay in comparison with HPLC-DAD was used. Results showed that the compound is absorbed via passive diffusion by paracellular pathway. The concentrations determined in the serosal (inside the sac) fluid by radioligand binding assay are in good agreement with those obtained through the widely used HPLC/MS protocol, demonstrating the reliability of the method. It is worthwhile to note that the radioligand binding assay allows detecting very low concentrations of analyte, thus offering an excellent tool to measure the intestinal absorption of receptor ligands. Moreover, the AR 170 quantity outside the gut sac and the interaction with A3 AR could presuppose good topical anti-inflammatory effects of this compound.